Non enzymatic NADH-dependent reduction of Cis-[Co(en)2(H2O)2]3+ in aqueous medium - Behera, Bharati; Behera, Jashoda (International Journal of Advanced Chemistry, 2018)
The kinetics of the electron transfer reaction of NADH with Cis-[Co(en)2(H2O)2]3+ has been studied over the range 1.0 â‰¤ 102 [NADH] â‰¤ 3.0 mol dm-3, 7.0 â‰¤ pH â‰¤ 8.0 and 200C â‰¤ t â‰¤ 350C in aqueous medium. The rate of electron transfer reaction was found to be first-order dependence each in [NADH]T and Cis-[Co(en)2(H2O)2]3+T. The products of the reaction were found to be NAD+ and Co(II). The corresponding activation parameters of the electron transfer reactions were found to be as Î”H#=27.55 kJ mol-1 and Â Î”S#= -189.35 JK-1mol-1.Â